PENGARUH EFISIENSI MODAL KERJA, LIKUIDITAS, DAN SOLVABILITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN FOOD AND BAVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA (Periode 2012-2018) - Tjiptowati Endang Irianti (BISECER (Business Economic Entrepreneurship), 2021)
Every company has a goal to increase its profitability. Profitability is the ability of a company to make a profit in relation to sales, total assets, and own capital. A stable profitability will make investors interested in investing their funds. Profitability can be measured by Return On Investments (ROI) obtained from profit after tax compared to total assets. Factors affecting company profitability are working capital efficiency, liquidity and solvency. This study aims to determine the effect of working capital efficiency, liquidity and solvency on the profitability of companies in food and beverage companies listed on the Indonesia Stock Exchange. The design of this study is casual associative research. The research population is all food and beverage companies listed on the Indonesia Stock Exchange for the 2012-2018 period. The sampling technique used was purposive sampling. The research population data is 15 companies and a sample of 14 companies is obtained. The independent variables in this study are working capital efficiency, liquidity and solvency. The dependent variable in this study is company profitability. Data analysis methods used are correlation, regression, determination, t test and F test with a significant level of 0.05. Based on the results of the analysis using multiple correlation test the relationship between efficiency of working capital, liquidity and solvency of company profitability with an R square value of 0.433 , this shows a fairly strong influence. The multiple linear regression equation in this study was formulated as Y = -80,823 + 3,259 WCT + 12,988 CR - 0,013 DER + e, working capital turnover and current ratio had a positive effect and the dept to equity ratio had a negative effect with a fixed assumption. Regression analysis yielded ajusted R² of 0.406 or 40.6%. While the remaining 59.4% is explained by other variables outside the model. Partial test (t test) variable working capital efficiency has a positive effect on company profitability with t arithmetic of 3636> t table 1.9971 and a significant value of 0.001, then Ho is rejected and H1 is accepted. Liquidity has a positive effect on company profitability with a t count of 5.101> t table 1.9971 and a significant value of 0.000, then the Ho area is rejected and H2 is accepted. Solvency has a negative effect on company profitability with a t count of -0.917< t table -1.9971 and a significant value of 0.363, then Ho is accepted and H3 is rejected. The accuracy of the model test results obtained calculated F value of 16.519> f table 2.74 with a significance value of 0.000